One-sheet spiraling full thickness skin graft for penile resurfacing after paraffinoma excision (Faculty of Medicine Universitas Indonesia, 2011)
In the midst of on-going non-illicit practice of silicone or paraffin injection to enlarge penis, the author reported 3 cases of surgical treatment to resurface the body of the penis after excision of the destructed penile skin using full thickness skin graft. The skin excision was performed technically through penile body degloving procedure. Full thickness skin graft was then applied as a single sheet donor tissue to cover the denuded penile body spirally. The full thickness graft, which is relatively easy to be performed, is no doubt much thinner than a skin flap, while it also bears a smaller degree of secondary contraction than split skin graft. The color of the skin is considerably matched as it comes from the groin, which is a nearby area of penis. The size and skin sensitization of the penis looks to be natural. The only disadvantage is the common possibility of either spiral or circular junctional scar in between graft edges and between the graft and the penile mucosa and skin to develop hypertrophic scar. However, this possible scar problem applies also to any other surgical scar with any donor tissue. Fortunately, the 3 cases posed no scar problem and normal appearance. All the patients have also regained their normal sexual function. (Med J Indones 2011; 20:222-5)